Legal Certainty for Digital Investors Through the Reconstruction of SupTech Based on Electronic System Reliability - Michael Lauvino; Ismiyanto Ismiyanto; Ariy Khaerudin (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Digital transformation has significantly increased the number of retail investors in Indonesia while simultaneously amplifying the risk of financial losses resulting from failures in digital investment service systems. However, the existing legal framework has not yet established adequate standards for ensuring the reliability of electronic systems. This study aims to analyze the regulatory framework governing cybersecurity and the financial services sector in providing legal protection for retail investors and to formulate a supervisory reconstruction model for the Financial Services Authority through the adoption of Electronic-Based Government System (SPBE) principles as the foundation for the development of Supervisory Technology (SupTech). This research employs a normative legal method using statutory, conceptual, analytical, and comparative approaches. The findings reveal regulatory gaps concerning electronic system reliability standards, parameters for determining system failures, and the allocation of liability among digital investment service providers. This study proposes a SupTech-based supervisory model that strengthens legal certainty, enhances preventive legal protection for retail investors, and promotes more accountable, transparent, and resilient digital investment governance.